CLINOPTILOLITE VS. ACTIVATED CARBON AS A METHOD OF REMOVING HEAVY METALS FROM WATERS - NEAMȚU, Corina Ioana; PIRĂU, Luminița Cristina; BOLUNDUȚ, Liviu Călin; PICĂ, Elena Maria; TĂNĂSELIA, Claudiu; CHIOREANU, Gelu (Studia Universitatis Babeș-Bolyai Ambientum, 2016)
Acid mine drainage (AMD) is considered a major risk for groundwater and soil pollution if discharged in the environment without prior treatment, as it contains important quantities of heavy metals. The paper presents an experiment conducted using the batch technique, for the removal of six metals (Cd, Pb, Cu, Ni, Al, Zn) from AMD at the interaction with two filtering materials [zeolite (Z) and activated carbon (AC)], without chemical treatment. The results showed that the zeolite removed successfully Al and Pb in proportion of 96%, and the AC proved to be very effective in removing five (Al, Cd, Cu, Zn and Pb) out of the six metals studied, in proportion of 97%. Ni is the most difficult metal to be removed regardless the filtering material used. Although, better results are achieved for this metal at the interaction with AC - 20.11%, compared to zeolite - 18.97%. The efficiency of the two materials is given by the interaction time with AMD.